The Nature Of Strategic Management - Dessy Boegiyati; Yunita Tri Wulandari; Mukhammad Saam Nabil Fairoby (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
Strategic management is a systematic and structured process that enables organizations to formulate, implement, and evaluate strategies to achieve long-term objectives in a dynamic business environment. This literature review examines the nature of strategic management, including its definition, key characteristics, implementation stages, and importance for organizational success. The study employs a qualitative approach through comprehensive literature analysis from academic sources, journals, and case studies. Findings indicate that strategic management comprises three main stages: strategy formulation, strategy implementation, and strategy evaluation and control. Key characteristics include long-term focus, holistic approach, dynamic adaptability, and competitive advantage orientation. The research demonstrates that strategic management is crucial for organizations to achieve competitive advantage, adapt to environmental changes, optimize resource allocation, enhance organizational coordination, improve financial performance, manage risks, and foster innovation and sustainable growth. Organizations implementing strategic management consistently show better financial performance than those without systematic strategic planning. These insights highlight strategic management as an essential investment for organizational success and sustainability in today's competitive business landscape.